2014
DOI: 10.1140/epjc/s10052-014-3081-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological discriminations of the Yukawa interactions in two-Higgs doublet models with $$Z_2$$ Z 2 symmetry

Abstract: There are four types of two-Higgs doublet models under a discrete Z 2 symmetry imposed to avoid tree-level flavor-changing neutral current, i.e. type-I, type-II, type-X, and type-Y models. We investigate the possibility to discriminate the four models in the light of the flavor physics data, including B s -B s mixing, B s,d → μ + μ − , B → τ ν and B → X s γ decays, the recent LHC Higgs data, the direct search for charged Higgs at LEP, and the constraints from perturbative unitarity and vacuum stability. After … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 127 publications
(190 reference statements)
1
19
2
Order By: Relevance
“…For the B s → μ + μ − decay, the correlations between its branching ratio and the mass-eigenstate rate asymmetry A are also reevaluated with the constrained parameter space of the 2HDMs obtained in this paper. We have found that A can slightly deviate from the SM prediction in the type-II 2HDM only, and that the ratio of time-integrated B(B s → μ + μ − ) gets similar contributions from the four 2HDMs; this makes it very hard to discriminate the four types of 2HDMs with the correlation between A and B(B s → μ + μ − ) as suggested in our previous work [64].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…For the B s → μ + μ − decay, the correlations between its branching ratio and the mass-eigenstate rate asymmetry A are also reevaluated with the constrained parameter space of the 2HDMs obtained in this paper. We have found that A can slightly deviate from the SM prediction in the type-II 2HDM only, and that the ratio of time-integrated B(B s → μ + μ − ) gets similar contributions from the four 2HDMs; this makes it very hard to discriminate the four types of 2HDMs with the correlation between A and B(B s → μ + μ − ) as suggested in our previous work [64].…”
Section: Introductionmentioning
confidence: 54%
“…Using the Higgs base correspondence between the A2HDM and the 2HDMs, we will derive the relevant full one-loop Wilson coefficients of the four variant 2HDMs contributing to the B s → μ + μ − decay from the recent A2HDM results [60] without the large tan β approximation. We also investigate the possibility to discriminate the four different types of 2HDM in the light of the recent collider and flavor physics data, as an update of our previous work [64]. We combine the constraints from [65,66], with the experimental data from the direct search for Higgs bosons at LEP [67], Tevatron [68,69] and LHC [70,71], and the constraints from perturbativity, tree-level vacuum stability and perturbative unitary.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we choose the light neutral Higgs boson h as the observed Higgs boson at the LHC and adopt the alignment limit [40][41][42][43]. For other choice that the heavy neutral Higgs H is observed one, we refer to ref.…”
Section: Methods Of Numerical Analysismentioning
confidence: 99%
“…In order to derive an allowed parameter space, we impose the experimental constraints in the same way as in refs. [42,52]: for each point in the theoretical parameter space we span the range of the theory prediction for an observable by performing the 2σ variations of input parameters. If the difference between the central values of theory prediction and experimental value is less then the sum of two errors in quadrature, then this point is regarded as allowed.…”
Section: Methods Of Numerical Analysismentioning
confidence: 99%
“…For the type II model we have also included constraints coming from R b measurements [74] as well as B meson decays [75][76][77][78] which prove to be very strong by setting m H + > 480 GeV independently of the value of tan β. For type I, since the red/green points have tan β > 10, these constraints do not impose any further restrictions [79,80]. We also checked that all points still respect simple bounded from below and perturbativity constraints [4].…”
Section: Jhep11(2017)106mentioning
confidence: 99%